1987
DOI: 10.1007/bf00210833
|View full text |Cite
|
Sign up to set email alerts
|

Effects of scopolamine and physostigmine on recognition memory in monkeys with ibotenic-acid lesions of the nucleus basalis of Meynert

Abstract: Monkeys with bilateral ibotenic-acid lesions of the nucleus basalis of Meynert, an area rich in cholinergic neurons that innervate the cerebral cortex, were compared with unoperated control monkeys on a recognition memory task. Although animals with large lesions had substantial reductions of cortical choline acetyltransferase activity, none showed impairment in the task. Lesion effects were observed, however, when performance was assessed following administration of a muscarinic receptor blocker (scopolamine)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Cholinergic agonists, cholinesterase inhibitors, and hippocampal grafts of cholinergic neurons have been reported to restore memory function after these lesions and to improve memory function in normal rats and mice (26)(27)(28)(29)(30). Our findings demonstrate that ACh infusion ivt or intrahippocampally can ameliorate a NBM-MSA lesioninduced memory deficit for a short period oftime and that this treatment can be effectively repeated in the same animal.…”
Section: Methodssupporting
confidence: 52%
“…Cholinergic agonists, cholinesterase inhibitors, and hippocampal grafts of cholinergic neurons have been reported to restore memory function after these lesions and to improve memory function in normal rats and mice (26)(27)(28)(29)(30). Our findings demonstrate that ACh infusion ivt or intrahippocampally can ameliorate a NBM-MSA lesioninduced memory deficit for a short period oftime and that this treatment can be effectively repeated in the same animal.…”
Section: Methodssupporting
confidence: 52%
“…More specifically, prefrontal ACh has been implicated in working memory processes as demonstrated by behavioral tasks including delayed nonmatching to sample (Broersen et al, 1995) and object recognition tests (Aigner et al, 1987;Giovannini et al, 1998;Scali et al, 1994). Furthermore, cognitive-enhancing drugs can increase ACh release in the prefrontal cortex (Scali et al, 1994;Yamamoto et al, 1994) whereas direct application of the muscarinic cholinergic receptor antagonist scopolamine into the frontal cortex (Mouton et al, 1988) or the hippocampus (Messer et al, 1991) impairs working memory.…”
Section: A Potential Role Of Da D 3 Receptors In the Effect Of Apds Omentioning
confidence: 99%
“…At doses higher than those proposed for incorporation in pretreatment regimens, scopolamine has been shown to affect performance on a range of cognitive tasks in rhesus monkeys (Aigner et al 1987;Taffe et al1999), and Ridley et al (1984) showed that administration of scopolamine resulted in both impaired acquisition of object-reward associations and impairments in transfer of that association to long-term memory in marmosets. Such object discrimination impairments in marmosets have been shown to be reversible by cholinergic agonists, such as arecoline (Carey et al 1992).…”
Section: Introductionmentioning
confidence: 97%